Optimising spent mushroom compost biochar for heavy metal removal: Mechanisms and kinetics in mine water treatment - Madzin, Zafira; Zahidi, Izni; Talei, Amin; Raghunandan, Mavinakere Eshwaraiah; Hermawan, Andreas Aditya; Karam, Daljit Singh (Elsevier, 2025)
Overpopulation and urbanisation have led to water crises, and abandoned mine water has become an alternative water source for some countries. This study optimises the potential of biochar derived from spent mushroom compost (SMC), a cost-effective and locally abundant biomass resource, to remove specific heavy metals (copper - Cu, manganese - Mn, iron - Fe, and lead - Pb) commonly found in abandoned mine water. SMC was pyrolysed into biochar at varying temperatures (300 °C, 500 °C, and 700 °C). Preliminary characterisation and in-depth batch studies were conducted to evaluate the properties of SMC biochar prepared at varying pyrolysis temperatures. Results indicate that SMC biochar effectively removes heavy metals, with varied performance based on pyrolysis temperature. The highest removal occurred at 500 °C for Cu (2.573 mg/g), Mn (1.522 mg/g) and Pb (2.491 mg/g). Batch studies revealed that adsorption performance depended on pH, pyrolysis temperature, and initial metal concentration. Langmuir and pseudo-second-order models fitted well (R2 > 0.99), confirmed monolayer adsorption driven by cation exchange, electrostatic interactions, and π-complexation mechanisms. These findings highlight the suitability of SMC biochar as an eco-friendly alternative to activated carbon for heavy metal removal. This research advances biochar applications in mine water treatment, contributing to sustainable development and water resource management.